BIG DATA ANALYSIS IN MARKETING AND ITS IMPLEMENTATIONS IN UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
One of the most important questions for using big data analysis in marketing today is widely discussed. In general, big data is not a novelty because it has successfully been used in various countries.